A review of literature of polymorphic eruption of pregnancy - Vadakkumpadam, Mohammed Haneefa; Abualiat, Abdullah Saeed; Sabrah, Tameem Abdullah (International Journal of Research in Dermatology, 2021)
Polymorphic eruption of pregnancy (PEP), also known as pruritic urticarial papules and plaques of pregnancy [PUPPP] is the most common of all the specific dermatoses of pregnancy. It is a benign, self-resolving, pruritic disorder of pregnancy, usually affecting primigravida during the last trimester of pregnancy or immediately postpartum. Its exact pathogenesis is still unknown, and its clinical presentations are variable. It may mimic many common dermatoses. In PEP, the histological findings are non-contributory and the laboratory results, including direct and indirect immunofluorescence are negative. Diagnosis mainly depends on clinical findings. Significant diagnostic confusion may occur with early lesions of pemphigoid gestationis, which needs to be differentiated from PEP as the former may have a bad fetal outcome. PEP is not associated with any fetal or maternal risk, and symptomatic treatment is all that is usually required. The awareness of this condition helps the physician recognize this entity, reassure the patient, and avoid unnecessary investigations. This review focuses on etiology, various clinical presentations, differential diagnosis, and management of PEP.